REFUGEE DETENTION CENTRE: HUMANITY VS NATIONAL SECURITY - Ninon Melatyugra (Universitas Kristen Satya Wacana, 2014)
AbstrakHukum internasional mengakui refugee sebagai suatu entitas yang memiliki kepentingan kemanusiaan selama mencari perlindungan di luar negaranya dari penyiksaan yang terjadi di negaranya. Sebagai konsekwensi, setiap negara mempunyai kewajiban erga omnes untuk memberi perlindungan terhadap para refugee di negara tersebut. Sayangnya dalam praktik, terdapat ketidakseimbangan antara kepentingan manusiawi dan kepentingan keamanan nasional. Artikel ini menunjukkan ketidakseimbangan kedua posisi dengan mengambil fokus pada Detention Centre di Australia, sebuah negara yang telah meratifikasi the 1951 Convention relating to the Status of Refugees. Penahanan administrasi dan ketidaktransparanan penilaian keamanan yang dilakukan oleh ASIO merupakan dua faktor utama berlatarbelakang keamanan nasional yang telah melemahkan posisi kepentingan kemanusiaan. Artikel ini juga menawarkan dua solusi untuk mengatasi masalah; pertama, batasan penahanan administratif harus dilakukan untuk menjamin hak hukum para refugee selama proses pengajuan visa; kedua, transparansi penilaian keamanan untuk menciptakan check-and-balance antara pemerintah Australia dan refugee dalammenentukan status visa para refugee. AbstractInternational law recognizes refugee as an entity who possesses humanity interest while seeking for asylum outside his/her country from persecution in his/her country. As a consequence, each state has an erga omnes obligation to give asylum to refugees in its country. Unfortunately in practice, there is a lack of balance between humanity interest and national security interest. This article shows the imbalance of both position by taking focus on Detention Centre in Australia, a country that has ratified the 1951 Convention relating to the Status of Refugees. Administrative detention and intransparency of security assessment exercised by ASIO are two main factors with the national security background that have weakened the position of humanity interest. This article also proposes two solutions to tackle the problems; first, limitation of administrative detention must be undertaken to guarantee refugees legal right during the visa application process; second, transparency of security assessment in order to create check-and-balance position between Australian Government and refugee in determining refugees visa status.